2016
DOI: 10.5937/ekonhor1603187t
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of the cointegration relation among the stock markets on the portfolio choices: An empirical application for fragile five countries

Abstract: The aim of this study is to examine the long-term relationship between each pair of the countries separate from those in the Stock Markets of Fragile Five Countries and determine the optimal portfolio options for each of the BIITS countries according to the pieces of evidence obtained. Thus, the reflection of the concertedness among financial markets to the optimal portfolio options has been studied. Accordingly, long term relationships between each pair of BIITS countries have been investigated with monthly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the previous study, Tuna (2016) found that there was a cointegration relationship between the stock exchanges of Fragile Five countries using the Maki Cointegration Test method using monthly stock price data from the period June 2006 to July 2015. This study also provides portfolio diversi ication recommendations through the long-term approach.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, Tuna (2016) found that there was a cointegration relationship between the stock exchanges of Fragile Five countries using the Maki Cointegration Test method using monthly stock price data from the period June 2006 to July 2015. This study also provides portfolio diversi ication recommendations through the long-term approach.…”
Section: Introductionmentioning
confidence: 99%